Outreach and performance analysis of microfinance institutions in Cameroon - Shu, Cletus Ambe; Oney, Bilge (Routledge Journals, Taylor & Francis Ltd, 2014)
Since people with low incomes do not have access to financial institutions, and in most developing countries only public workers benefit from the services of public banks, the poor and private workers with low incomes cannot borrow from these public banks. Hence, microfinancial institutions (MFIs) have become the answer to those who cannot benefit from the financial services of the public banks. This study compares the performance and outreach aspect of the MFIs in Cameroon against the African benchmark. Furthermore, it investigates if there is a trade-off between performance and outreach. A total of six selected MFIs with branches all over Cameroon were chosen for this study. Using the difference of mean test, the findings of the study revealed that generally, the MFIs in Cameroon implemented a low cost strategy and are heavily exposed to default risk. We also concluded a trade-off between the performance and outreach factors. MFIs in Cameroon are more focused on making profits, instead of reaching out to the poorest of the poor in the communities.
Keywords: microfinance; Cameroon; outreach; performance analysis; poor; financial insitutions